Development of Augmented Reality Media on PjBL Learning Model of Human Motion Organ Material to Improve Learning Outcomes - Maulidannisa, Naila; Ansori, Isa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to develop and test the feasibility and effectiveness of AR-based learning media (augmented reality) so that students become more active in following the learning process. This research and R&D (Reseacrh and Development) with the ADDIE development model design. The novelty of this research is the development of Human Movement Organs (bones) with interactive edugame evaluations that improve students' cognitive learning outcomes. Analysis of the data obtained after the research stages are carried out. The results showed that AR-based learning media (augmented reality) was successfully developed, feasible, and effective to use as learning media, seen from the results of media validation obtained a percentage of 84.72%, material validation obtained a percentage of 83.30% and student response obtained a percentage of 88.46%. The conclusion of the Augmented Reality media development research on the PjBL learning model of Human Movement Organ material was successfully developed, very feasible, and effective for improving the learning outcomes of Nabaul Ulum Wonorejo students in Pati Regency.